Dual stimuli-responsive oligo(ethylene glycol)-based microgels: insight into the role of internal structure in volume phase transitions and loading of magnetic nanoparticles to design stable thermoresponsive hybrid microgels. Issue 2 (3rd November 2015) - Boularas, Mohamed; Deniau-Lejeune, Elise; Alard, Valérie; Tranchant, Jean-François; Billon, Laurent; Save, Maud
Abstract : Design of multi-responsive biocompatible P(MEO2 MA- co -OEGMA- co -MAA) microgels and their hybrid magnetic couterparts. Abstract : Multi-responsive biocompatible microgels with long term stability were synthesized by precipitation copolymerization of oligo(ethylene glycol) methyl ether methacrylate (OEGMA), di(ethylene glycol) methyl ether methacrylate (MEO2 MA), methacrylic acid (MAA) and crosslinkers in aqueous dispersed media. Different crosslinkers, i.e. ethylene glycol dimethacrylate (EGDMA), oligo(ethylene glycol) diacrylate (OEGDA) or N, N -methylenebisacrylamide (MBA) were used for the synthesis of the microgels. The present work investigates for the first time how the inner structure of the biocompatible P(MEO2 MA- co -OEGMA- co -MAA) microgels impacts their swelling-to-collapse transition in response to both temperature and pH. The EGDMA-crosslinked microgels obviously differ from the OEGDA- and MBA-crosslinked microgels. The OEGDA-crosslinked P(MEO2 MA- co -OEGMA- co -MAA) microgels are ideal candidates to prepare robust thermoresponsive hybrid magnetic microgels by a straightforward method involving simple loading of pre-formed magnetic nanoparticles (NP) in the absence of NP release. The crosslinker distribution is at the origin of differences in the distribution of iron oxide nanoparticles. The homogeneous distribution of both MAA units and the OEGDA crosslinker in the P(MEO2 MA- co -OEGMA- co -MAA) microgels ensured a sharp VPTT of microgels over a wide range of pH values (from pH 4 to 9) and the retention of the thermoresponsiveness of the corresponding hybrid microgels for the different contents of magnetic nanoparticles (from 7 to 33 wt% of γ-Fe2 O3 versus polymer). Turbidimetry measurements highlighted the unique stability of the hybrid microgels over several hours even for the highest content of iron oxide nanoparticles.